An Investigation of The Forests of Pernik Province (Western Bulgaria) by The Use of The Perpendicular Vegetation Index (PVI) - Grigorov, Borislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The current research represents a pilot study for application of the Perpendicular Vegetation Index (PVI) for an area with forests in Bulgaria. It is the first of its kind when it comes to forest studying in the country to the best knowledge of the author. When it comes to soil background Landsat images and other spectral data may be used for monitoring forest territories as well. The study area is Pernik Province which is located in the western parts of Bulgaria.
Keywords: remote sensing; biomass; vegetation index; Landsat; teledetekcja; biomasa; wskaźnik roślinności; Bułgaria Zachodnia